Recipe for a perfect wife : a novel - Brown, Karma (Dutton, 2020)
A dual narrative in which a woman finds a cookbook buried in the basement of her new home and becomes captivated with the cookbook's previous owner, a 1950s housewife. Dissatisfied with her own life, she becomes absorbed in learning the story--and the secrets--of the last woman who lived in her house.